A dual iron-ring double-stator permanent magnet integrated with a magnetic gear for low speed power generator - Salihu, Mustafa Shehu (2018)
Magnetic gears and magnetic geared permanent magnet (PM) machines have recently been emerging as a new class of future electromechanical machines which can address problems of low-speed power generators. A magnetic geared generator integrates a magnetic gear with a low torque, high-speed PM generator to produce a compact lowspeed, high torque machine with the advantages of a direct drive PM machine and magnetic gear. Although, previous low-speed PM generators designed with high number of poles and magnetic geared generators both eliminate the use of a mechanical gear, their power density capacity is low to generate sufficient electrical power for low-speed applications. The proposed magnetic geared generator with high power density due to the dual-iron ring is specifically aimed to address problems of low-power density in low-speed power generators. A magnetically coupled configuration structure is implemented in the generator design with dual-iron rings and three layers of mutual PMs. This configuration enables the three PMs achieve total flux-linkage in both outer and inner machines, therefore increasing the number of air gaps and power density. The proposed machine operates simultaneously as a magnetic gear and electrical power generator. A two dimensional finite element method (2D FEM) is used to study and predict the performance characteristics of the magnetic geared generator. A prototype of the magnetic geared generator is fabricated and experimentally evaluated, for performance parameters such as transmission torque, electrical power-speed characteristics and efficiency. In addition, the proposed magnetic-geared generator is compared with previous magnetic-geared generators and the effectiveness is verified by using power density evaluation. It is found from the measured results that the magnetic geared PM generator with an active stack length of 30 mm, size of 150 mm and active volumetric density of 393 cm3 achieved maximum DC power and AC power of ≈ 250 W and ≈ 360 W, respectively. The maximum torque achieved on DC load and AC load are ≈ 12 Nm and ≈ 11 Nm respectively, with an efficiency of ≈ 55% at prime speed of 250 rpm on DC load and ≈ 52% at prime speed of 250 rpm on AC load, with a power factor of 0.99 respectively. The magnetic geared PM generator demonstrates overload protection by slipping at prime speed in excess of 500 rpm. In addition, the magnetic geared PM generator was found to achieve a measured maximum active power density of ≈ 917 kW/m3. The calculated and measured results are in good agreement to verify the validity of the proposed magnetic geared generator design. The proposed magnetic-geared generator has a higher power density than the previous magnetic-geared generators. Also, the maximum electrical power of the proposed magnetic-geared generator is sufficient for low-speed applications. The power due to the dual-iron rings is greater than the early magneticgeared generators.